Fenomena Dan Faktor Penyebab Masifnya Praktik Politik Uang Pada Pemilu di Provinsi Banten - Ikrimatul Amal (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
Elections as a form of implementation of the existing democratic system in our country, this is clearly stated in the 1945 Constitution paragraph 1 Article 2 which reads sovereignty is in the hands of the people and is carried out according to the Basic Law. Money politics is interpreted as a simple economic exchange, can be interpreted in different contexts in each different culture depending on how the community views This research aims to describe how the phenomena of massive money politics practice occur in Banten Province in every election event and the factors that cause money politics to still be carried out and what efforts have been made by Bawaslu in dealing with the practice of money politics. The method used is the study of literature from various journals that are in accordance with the research focus as well as research-related books and articles from various existing websites.